The Development of Electronic Student Worksheet Based on Multiple Intelligences on Human Heredity Materials to Increase Learning Outcomes for 12th Grade Students - Wahyu sifasari; Guntur Trimulyono (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Human heredity material is difficult for some students because it is invisible and complex. Understanding difficulties can make students' experience in learning outcomes decreased. Therefore, learning media needed to increase motivation and adaptable to students' learning styles, such as the electronic student worksheet (Lembar Kerja Peserta Didik Elektronik/ e-LKPD) based on Multiple Intelligences. This study aimed to produce Multiple Intelligences e-LKPD on human heredity material, which is feasible in validity, practicality, and effectiveness to improve student learning outcomes. This study used 4D methods and tested on 20 students of 12th of SMAN 8 Surabaya students. The data was analyzed through the quantitative- descriptive technique. The research results got a very valid category with a 3.86 score for product validation and a 100% very valid category for the suitability of the material with the selected type of intelligence. The practical aspect got a very practical category with a 97.3% score. On the aspect of effectiveness, it is reviewed from four things, namely the N-gain test, the sensitivity of items, the completeness of multiple intelligences, and the students' response, with a score of 0.92, 0.66, 91.25%, and 99%, each categorized as high, sensitive, very high, and very effective category respectively. Thus, this e-LKPD can be used in the current learning process based on the students' specific multiple intelligence abilities and as an additional reference for teachers to teach human heredity material.